2014
DOI: 10.4103/2348-0548.124850
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dexmedetomidine and lignocaine on attenuation of airway and pressor responses during tracheal extubation

Abstract: Background: Haemodynamic stability and rapid emergence after general anaesthesia used in spinal surgery is a common practice, the goal of which is to permit early neurological motor and sensory examination. Extubation is almost always associated with hypertension, increased airway response and arrhythmias. We have compared the effects of the α-2 agonist Dexmedetomidine and Lignocaine given at the end of the procedure on attenuation of airway and pressor responses following tracheal extubation. This study is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
1
27
1
Order By: Relevance
“…This is in conjunction with the study done by Sharma VB. 14 Our study found insignificant difference in the incidence of vomiting between two groups.…”
Section: Discussioncontrasting
confidence: 51%
“…This is in conjunction with the study done by Sharma VB. 14 Our study found insignificant difference in the incidence of vomiting between two groups.…”
Section: Discussioncontrasting
confidence: 51%
“…4 Different drugs and methods have been used to prevent haemodynamic response during extubation such as local anaesthetics, calcium channel blockers and vasodilators. [5][6][7] Dexmedetomidine hydrochloride is a highly selective, specific and potent α2 adrenergic agonist (1620:1 2 to 1) drug which is S-enantiomer of medetomidine. 8 It decreases the sympathetic outflow and noradrenergic activity thereby decreasing blood pressure and heart rate.…”
mentioning
confidence: 99%
“…29 In another study, dexmedetomidine was compared with lignocaine and normal saline in extubation and concluded that the use of dexmedetomidine was associated with less increase in HR as compared to lignocaine group, MAP was better controlled in the dexmedetomidine group than in lignocaine group and airway response was better controlled with the use of dexmedetomidine providing a smooth and easy tracheal extubation, thereby a more comfortable recovery and early neurological examination. 30 In another study, there was a significant decrease in MAP and HR in Dexmedetomidine group as compared to group Lignocaine and group Placebo (p<0.05) at all-time interval after extubation. Extubation quality score of the majority of patients was 1 in group DEX, 2 in group Lignocaine and 3 in group Placebo.…”
Section: Discussionmentioning
confidence: 87%